THE DEPLETION TIME OF THE WATER TANK: A MATHEMATICAL MODEL AND ITS EXPERIMENT - (NIM: 20107092), IRMAWATI
An experiment was carried out to determine the depletion time of the tank. The result of the experiment was analized using Excel program and then compared by using a mathematical model of the emptying tank. The result of Excel program has a good agreement with the mathematical model of the emptying tank.